(untitled) (Revista horizonte, 2014)
Context: Heart rate recovery (HRR) is associated with parasympathetic reactivation. Obtain sensitive indicators of vagal activity is important to control internal training loads. Purpose: To compare different indicators of HRV in the time domain related to vagal activity and determine what could be more appropriate for assessing parasympathetic reactivation after maximal exercise in healthy trained subjects. Methods: Nine male subjects performed an incremental test with an initial velocity of 7 km h- 1 and an inclination of 0%. The speed was increased every minute in 1 km h-1 until exhaustion to obtain the peak treadmill velocity (PTV). Linear analysis of HRV was assessed using root mean square of the difference of successive R-R intervals (rMSSD) and standard deviation of normal R-R intervals (SDNN), and nonlinear analysis of HRV was assessed by standard deviation of instantaneous (SD1) beat-to-beat R-R interval variability. In addition, the HRR was calculated at 30 and 60 s (Î”HRR30s and Î”HRR60s respectively). Results: Significant differences between SDNN and rMSSD (p <0.001) and between SDNN and SD1 (p <0.001), both at 30 and 60 seconds were found. No differences between rMSSD and SD1 at any time were observed. There were also significant differences in the kinetics of SDNN between time 0 and 30 s (2.77 Â± 0.6 and 9.7 Â± 4.7 ms, respectively; P <0.001). No differences in the kinetics of rMSSD and SD1 found during recovery at any time. Conclusions: The results suggest that in young, healthy and trained subjects the time domain index SDNN is a good indicator of parasympathetic reactivation immediately after maximal exercise when is compared to other indices as rMSSD and SD1.